IDENTITAS KOTA DAN PARIWISATA: MENAFSIR ULANG “SOLO THE SPIRIT OF JAVA” - Agus Saputro (STABN Raden Wijaya Wonogiri, 2022)
Identity is a distinctive identity attached to an object. Objects here can be material and non-material, with a character that the person will know and remember objects more easily. In this paper, the object studied in the city, with an identity formed through a tagline or